2016
DOI: 10.1007/s00441-016-2496-5
|View full text |Cite
|
Sign up to set email alerts
|

Decreased activation of placental mTOR family members is associated with the induction of intrauterine growth restriction by secondhand smoke in the mouse

Abstract: Cigarette smoke is known to be a risk for the development of intrauterine growth restriction (IUGR). Our objective was to assess the effects of secondhand smoke (SHS) during pregnancy and to what extent it regulates the activation of mTOR family members and murine trophoblast invasion. Mice were treated to SHS for 4 days. Placental and fetal weights were recorded at the time of necropsy. Immunohistochemistry was used to determine the level of placental trophoblast invasion. Western blots were utilized to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…mTORC1 signaling pathway has been considered as a nutrient sensor in the placenta. It has been well studied that placental mTORC1 activity was decreased in IUGR model [6,21], but few studies were taken to investigate the placental mTROC1 changes in pregnancies complicated with diabetes. Our results found that the activity of placental mTORC1 was significantly reduced in a rat model with severe pregestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 signaling pathway has been considered as a nutrient sensor in the placenta. It has been well studied that placental mTORC1 activity was decreased in IUGR model [6,21], but few studies were taken to investigate the placental mTROC1 changes in pregnancies complicated with diabetes. Our results found that the activity of placental mTORC1 was significantly reduced in a rat model with severe pregestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to ETS during pregnancy leads to a deregulation of the placental and umbilical cord blood transcriptome in humans . Along this line, a 4‐day exposure to ETS in the last trimester of murine pregnancy decreased placental and fetal weights, which was accompanied by decreased placental activation of the mechanistic Target of Rapamycin (mTOR) family of proteins which are involved in regulation of cell growth via nutrient sensing . Another study demonstrated an increase of substance P airway innervation, neuropeptide Y (NPY) protein levels and density of NPY fibres in the lung, as well as pulmonary levels of nerve growth factor (NGF) later in life after prenatal and early postnatal ETS, which was paralleled by lower lung function .…”
Section: Models Of Sidestream Cigarette Smoke Exposure During Pregnancymentioning
confidence: 99%
“…As prohibition of smoking in public places is incomplete in many countries, pregnant women can be exposed to environmental tobacco smoke ([ETS], experimentally corresponding to sidestream smoke) at public places as well as at home. ETS is a known risk factor for asthma (reviewed in) and lower birth weight which is also seen in mice …”
Section: Models Of Sidestream Cigarette Smoke Exposure During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Cord blood concentrations of essential amino acids are decreased in growth-restricted babies (Jansson et al 2012;Lin et al 2012;Diaz et al 2014;Dimasuay et al 2016), which also often present with hypoglycaemia (Economides & Nicolaides, 1989;Jansson et al 2012;Diaz et al 2014), with both of these outcomes likely due to alterations in placental abundance and localization of glucose and amino acid transporters (Glazier et al 1997;Janzen et al 2013;Cuffe et al 2014;Gardebjer et al 2014;Dimasuay et al 2016;Zhang et al 2016). Interestingly, mTOR signalling is also downregulated in the placenta of IUGR humans (Roos et al 2007;Jansson et al 2012;Diaz et al 2014;Fahlbusch et al 2015) as well as in animal models of reduced fetal growth (Jansson et al 2012;Dimasuay et al 2016;Zhang et al 2016;Mejia et al 2017;Rosario et al 2017). Animal studies have eloquently demonstrated that the disease burden of being born small is not limited to the first directly affected generation (F1), but can be transmitted across generations (Aerts & Van Assche, 2006;Gallo et al 2012Gallo et al , 2013Cheong et al 2016a).…”
Section: Introductionmentioning
confidence: 99%